PERSEPSI PETANI TERHADAP KELEMBAGAAN PENYULUHAN POLA SISTEM INTEGRASI SAPI¬¬–KELAPA SAWIT (SISKA) DI KABUPATEN PELALAWAN - Joko Saputra; Susy Edwina; Evy Maharani (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2016)
The purpose of this research is; (1) Identify existing institutions at the local level that can be utilized in the implementation of the integration of cow and palm oil based institutional capacity. (2) to analyze the perception of farmers towards institutional support system integration cattle and palm oil . This study was conducted in Pelalawan, Riau province, exactly in the three groups which apply SISKA program and did not apply this SISKA program. The method used is the census. Total sample of 35 farmers consisting of farmer group chairman, secretary, treasurer and members of farmer groups. Analysis of the data for the purposes of the first to use the descriptive method, and the second objective Summated using Likert Scale Rating (SLR). The results showed: The role of institutional Extension overall quite instrumental in supporting farmer groups cow and palm oil, consisting of indicator education and dissemination of information are in the category of acts, facilitation, supervision, and monitoring are in the category of less instrumental, while the consultations are in the category enough play. Keywords: Perception, institutional, extension, integration